Attitude Research in Accounting: A Model for Reliability and Validity Considerations. - Grove, Hugh D.; Savich, Richard S. (The Accounting Review, 1979)
Abstract Attitude research in accounting has utilized numerous methodologies to study various topics of interest. However, the substantiation of the research techniques sometimes leaves a void which obscures the results, This paper presents a model which, if followed, allows for reliability and validity tests to be conducted which provide for acceptance of the attitude scales as viable measurement and theoretical research methods. When acceptable instruments are employed, the concepts tested can then enhance the goal of theoretical advancement. The instrument-issue controversy is dealt with through a review of attitude research in accounting. Positive comments and constructive criticisms are made. The "so-what" question of construct validity is analyzed: does it really matter if accounting attitude research is undertaken ? The implication is that if the researcher does not consider the guidelines of the attitude model, the "so-what" issue may negate the potential contribution of such research.